Trimethylamine N-oxide (TMAO) acutely alters ionic currents but does not increase cardiac cell death - Esposito, Simona; McGuinness, Lauren R.; Sharma, Parveen; Chadwick, Amy E.; Rainbow, Richard D. (Frontiers in Physiology, 2025)
BackgroundTrimethylamine N-oxide (TMAO) is a product of the action of gut microbiota on choline and other choline-containing compounds ingested in the diet. The presence of TMAO at high concentrations has been reported in the blood of patients with cardiovascular disease, suggesting the role for TMAO as either a marker or causative agent of the disease. These investigations examined whether TMAO had an effect on cardiomyocyte contractile function, calcium homoeostasis, and survival from metabolic insult.ResultsTMAO had no effect on metabolic function or the ability of cells to survive a metabolic insult; however, it did cause transient changes to contractile function. These changes included an increase in calcium current and an increase in Kir6.1 channel activity in the cell, causing a shortening of the action potential duration to 90% repolarised but lengthening the action potential to 30% repolarised. These effects occurred within minutes of TMAO application; however, they were not observed following 24 h culture. These data suggest that TMAO does modulate contractile function, albeit only in the short-term, but has no effect on metabolic behaviour or the ability to withstand a metabolic challenge.ConclusionThese data suggest that high TMAO concentrations in the blood of patients may be a marker of potential cardiovascular disease rather than playing a causative role.